2020
DOI: 10.12659/msm.923549
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Support on Sleep Quality of Medical Staff Treating Patients with Coronavirus Disease 2019 (COVID-19) in January and February 2020 in China

Abstract: Background:Coronavirus disease 2019 , formerly known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and 2019 novel coronavirus (2019-nCoV), was first identified in December 2019 in Wuhan City, China. Structural equation modeling (SEM) is a multivariate analysis method to determine the structural relationship between measured variables. This observational study aimed to use SEM to determine the effects of social support on sleep quality and function of medical staff who treated patients with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

70
877
9
84

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,039 publications
(1,143 citation statements)
references
References 35 publications
70
877
9
84
Order By: Relevance
“…The risk of developing OCD seemed to increase by 64.6% for every increase in the level of sleep latency. People were reported to have many sleep problems during the quarantine, which may have been associated with the risk of developing OCD ( 15 , 16 ). Consistent with this, in our study, many patients with OCD had disturbing thoughts and repetitive performances like counting or making the bed, which in turn influenced the development of OCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of developing OCD seemed to increase by 64.6% for every increase in the level of sleep latency. People were reported to have many sleep problems during the quarantine, which may have been associated with the risk of developing OCD ( 15 , 16 ). Consistent with this, in our study, many patients with OCD had disturbing thoughts and repetitive performances like counting or making the bed, which in turn influenced the development of OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Social support and sleep quality have been linked to mental health in many previous studies; enough social support and good sleep quality could ensure a better mood ( 15 , 16 ). However, the association between them seems to be complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The research team developed a general information questionnaire based on a literature review. 6 , 11 , 12 An expert panel evaluated the questionnaire content; the panel included a fever clinic nurse, an emergency nurse, two head nurses, a nurse administrator, and two nursing professors. This questionnaire consisted of two parts; one was demographic characteristics (ie, sex, age, education level, designation, marital status, and having children); the other related to socio-psychological and working conditions during the COVID-19 pandemic, including rest time per week, the number of night shifts in the previous month, professional attitude, confidence, willingness to fight transmission, whether they have been in contact with confirmed patients, and whether they had recently attended infection prevention training.…”
Section: Methodsmentioning
confidence: 99%
“…In public health crises, several factors influence the mental health status of nurses. Common risk factors that cause stress and anxiety during a pandemic include a lack of effective hospital management systems, 10 lack of personal protective equipment (PPE) and training, 11 exposure to confirmed cases, 6 , 12 fear of being infected, 13 fear of spreading the virus to family members, 14 concerns about their children for not being taken care of, 15 long working hours, and heavy workloads. 9 , 13 Previous studies showed that the effect on mental health varies by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have assessed the different aspects of sleep by providing important information about its association with the pandemic 33 – such as the prevalence of sleep disturbance in different populations 8 , 15 , 34 and the potential risk factors for poor sleep quality during lockdown (eg, gender, level of education, occupational condition, social capital). 35 , 36 , However, no research has integrated the psychological variables into a model capable to associate the pandemic dimensions and the quality of sleep.…”
Section: Introductionmentioning
confidence: 99%